2003
DOI: 10.1007/s10096-003-1027-y
|View full text |Cite
|
Sign up to set email alerts
|

External Quality Control of Direct Antigen Tests to Detect Group A Streptococcal Antigen

Abstract: Presented here are the results of an external quality control survey organized by the Swiss Center for Quality Control (CSCQ) to evaluate the performance of direct antigen tests (DATs) widely used in Swiss medical practices and laboratories for the diagnosis of group A streptococcal pharyngitis. Twice yearly over a 4-year period, just over 100 participants were requested to analyze positive, weakly positive and negative samples provided to them by the CSCQ with their routinely used DATs and to send the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Several studies have shown that participation in an EQAS for POCT analyses is useful to improve analytical quality; e.g., for mononucleosis tests and urine dip-slide tests in Norway (8,9), for group A streptococcus tests in Finland (10) and in Switzerland (11), for hemoglobin tests in Belgium (12) and for blood glucose tests in Germany (13). The United Kingdom National External Quality Assessment Service (UKNEQAS) has reported their experience with EQAS for POCT INR over a 6-year period, and stated that this kind of control is both possible and necessary for health care professionals to obtain good analytical quality (14).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that participation in an EQAS for POCT analyses is useful to improve analytical quality; e.g., for mononucleosis tests and urine dip-slide tests in Norway (8,9), for group A streptococcus tests in Finland (10) and in Switzerland (11), for hemoglobin tests in Belgium (12) and for blood glucose tests in Germany (13). The United Kingdom National External Quality Assessment Service (UKNEQAS) has reported their experience with EQAS for POCT INR over a 6-year period, and stated that this kind of control is both possible and necessary for health care professionals to obtain good analytical quality (14).…”
Section: Introductionmentioning
confidence: 99%
“…Чем ниже оценка по клинической шкале и чем меньшее число БГСА, тем менее чувствительна система [19,20]. В различных условиях чувствительность экспресс-тестов может колебаться в пределах 10-95%, а специфичность -в пределах 90-100% [10,21]. В 2010 г. в России зарегистрирован Стрептатест производства французской фармацевтической компании «Dectra» -качественный иммунохроматографический тест для выявления антигенов стрептококка группы А, относится к экспресс-тестам второго поколения.…”
Section: серологическая классификацияunclassified
“…A comparative study showed that this RSAT had the highest sensitivity and specificity in ambulatory medical practice. 21 Throat cultures were incubated on 2 blood agar plates in anaerobia without inhibitor and were read after 48 hours in the Laboratory of Bacteriology, University Hospital of Geneva. Physicians prescribed antibiotic treatment immediately in all patients with positive RSAT results or within 48 hours in patients with a positive throat culture.…”
Section: Data Collectionmentioning
confidence: 99%